2017
DOI: 10.1190/geo2016-0162.1
|View full text |Cite
|
Sign up to set email alerts
|

Elastic internal multiple analysis and attenuation using Marchenko and interferometric methods

Abstract: Conventional seismic processing aims to create data that contain only primary reflections, whereas real seismic recordings also contain multiples. As such, it is desirable to predict, identify, and attenuate multiples in seismic data. This task is more difficult in elastic (solid) media because mode conversions create families of internal multiples not present in the acoustic case. We have developed a method to predict prestack internal multiples in general elastic media based on the Marchenko method and convo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 44 publications
(49 reference statements)
0
16
0
1
Order By: Relevance
“…Marchenko imaging (Behura et al . ; Broggini, Snieder and Wapenaar , ; Meles, Wapenaar and Curtis ; da Costa Filho, Meles and Curtis ; Singh et al . ; Thorbecke, van der Neut and Wapenaar ; Wapenaar et al .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Marchenko imaging (Behura et al . ; Broggini, Snieder and Wapenaar , ; Meles, Wapenaar and Curtis ; da Costa Filho, Meles and Curtis ; Singh et al . ; Thorbecke, van der Neut and Wapenaar ; Wapenaar et al .…”
Section: Introductionunclassified
“…The downward projections of the continuous light blue arrows, depicted by the dashed light blue arrows, describe the origin of ghost reflectors -dark grey dashed horizontal line -created because of the single-scattering assumption incorporated by the conventional imaging methods (Modified from Behura et al, 2014). Wapenaar 2014a, 2014b;Meles, Wapenaar and Curtis 2016;da Costa Filho, Meles and Curtis 2017;Thorbecke, van der Neut and Wapenaar 2013;Wapenaar et al 2014b) shows up as a novel target-oriented method that takes multiples into account and provides cleaner images with more reliable amplitudes. Although some limiting assumptions have to be made (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Marchenko methods have recently been used for a variety of purposes, including internal mul-tiple attenuation da Costa Filho et al 2017), target-oriented imaging Ravasi et al 2016), overburden elimination (van der Neut & Wapenaar 2016), synthesizing primaries , and virtual subsurface wavefield estimation . Its has also been extensively used for imaging (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that linear imaging of the redatumed data is equivalent to the imaging of primaries (Wapenaar et al, 2017). Hence, Marchenko imaging can also be interpreted as an internal multiple elimination process (Meles et al, 2015;van der Neut and Wapenaar, 2016;da Costa Filho et al, 2017). However, it has also been recently shown that novel imaging conditions can be derived for multiply reflected waves, given that a detailed model of the subsurface is available (Halliday and Curtis, 2010;Fleury and Vasconcelos, 2012;Ravasi et al, 2014Ravasi et al, , 2015b.…”
Section: Motivationmentioning
confidence: 99%